IgA1 hinge-region clustered glycan fidelity is established early during semi-ordered glycosylation by GalNAc-T2 - Stewart, Tyler J; Takahashi, Kazuo; Whitaker, Robert H; Raska, Milan; Placzek, William J; Novak, Jan; Renfrow, Matthew B (Glycobiology, 2019)
GalNAc-type O-glycans are often added to proteins post-translationally in a clustered manner in repeat regions of proteins, such as mucins and IgA1. Observed IgA1 glycosylation patterns show that glycans occur at similar sites with similar structures. It is not clear how the sites and number of glycans added to IgA1, or other proteins, can follow a conservative process. GalNAc-transferases initiate GalNAc-type glycosylation. In IgA nephropathy, an autoimmune disease, the sites and O-glycan structures of IgA1 hinge-region are altered, giving rise to a glycan autoantigen. To better understand how GalNAc-transferases determine sites and densities of clustered O-glycans, we used IgA1 hinge-region (HR) segment as a probe. Using LC-MS, we demonstrated a semi-ordered process of glycosylation by GalNAc-T2 towards the IgA1 HR. The catalytic domain was responsible for selection of four initial sites based on amino-acid sequence recognition. Both catalytic and lectin domains were involved in multiple second site-selections, each dependent on initial site-selection. Our data demonstrated that multiple start-sites and follow-up pathways were key to increasing the number of glycans added. The lectin domain predominately enhanced IgA1 HR glycan density by increasing synthesis pathway exploration by GalNAc-T2. Our data indicated a link between site-specific glycan addition and clustered glycan density that defines a mechanism of how conserved clustered O-glycosylation patterns and glycoform populations of IgA1 can be controlled by GalNAc-T2. Together, these findings characterized a correlation between glycosylation pathway diversity and glycosylation density, revealing mechanisms by which a single GalNAc-T isozyme can limit and define glycan heterogeneity in a disease-relevant context.
Keywords: lidé; Polysaccharides; IgA1 hinge region; biokatalýza; Polypeptide N-acetylgalactosaminyltransferase; GalNAc-transferase; Biocatalysis; clustered glycosylation; Humans; O-glycosylation; polypeptid-N-acetylgalaktosaminyltransferasa; polysacharidy; restricted glycan heterogeneity; Glycosylation; glykosylace; N-acetylgalaktosaminyltransferasy; N-Acetylgalactosaminyltransferases; imunoglobulin A; Immunoglobulin A